2001
DOI: 10.1002/ijc.1581
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk in persons receiving prescriptions for paracetamol: A Danish cohort study

Abstract: The use of paracetamol has been associated with increased risks for urinary tract cancers and decreased risk for ovarian cancer, although results have been inconsistent. We conducted a population-based cohort study using data from the Prescription Database of North Jutland County and the Danish Cancer Registry. Cancer incidence among 39,946 individuals receiving prescriptions for paracetamol was compared with expected incidence based on the North Jutland population who did not receive paracetamol prescriptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 27 publications
6
74
1
Order By: Relevance
“…Harris et al (1999) reported an OR of 0.84 among paracetamol users in a cohort of 32 505 women. Additionally, paracetamol has been previously linked to a decreased risk of ovarian cancer, another hormone-related cancer (Cramer et al, 1998;Rodriguez et al, 1998;Friis et al, 2002). In our study, we observed that users of paracetamol presented a reduced risk of breast cancer.…”
Section: Discussionsupporting
confidence: 61%
“…Harris et al (1999) reported an OR of 0.84 among paracetamol users in a cohort of 32 505 women. Additionally, paracetamol has been previously linked to a decreased risk of ovarian cancer, another hormone-related cancer (Cramer et al, 1998;Rodriguez et al, 1998;Friis et al, 2002). In our study, we observed that users of paracetamol presented a reduced risk of breast cancer.…”
Section: Discussionsupporting
confidence: 61%
“…39,40 The clinical data on this association, however, are limited and conflicting. 4,13,35,41 When interpreting these discrepancies, our lack of information on over-the-counter acetaminophen should be taken into account. Given the high skin cancer incidence and the widespread and frequent use of NSAIDs, a preventive effect of these agents may have important public health implications.…”
Section: Discussionmentioning
confidence: 99%
“…In observational studies, the association between commonly used anti-inflammatory drugs and ovarian cancer remains unclear. A Danish cohort study found no evidence of a protective effect of paracetamol [53], and a case-control study conducted in the USA concluded that, although non-significant, the observed risk estimates appeared to be compatible with a small decrease of risk by regular (more than three times a week for a period of at least 6 months) aspirin use [54].…”
Section: Use Of Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 95%